COLLABORATION AMONG FARMER’S AND INTERMEDIARY TRADERS IN MARKETING OF GREENHOUSE HYDROPONIC PRODUCTS IN GREATER MALANG - Dewi, Ni Made Gita Santhika; Susrusa, Ketut Budi; Arisena, Gede Mekse Korri; Bakhtiar, Ary (Faculty of Animal and Agricultural Science, Diponegoro University, 2024)
The emergence of negative effects associated with conventional agriculture encourages a transition from conventional to modern agriculture. Hydroponic farming, which utilizes water as a growing medium, is one form of modern agriculture. This research aimed to find out the management of farming business governance of hydroponic greenhouse products in Greater Malang, which includes commodities marketed, marketing institutions involved, the form of marketing channels that occur, and marketing functions used by analyzing marketing margins and farmer's share and knowing the corporate system between traders of hydroponic greenhouse products in Greater Malang. This study analyzed the data using qualitative and quantitative descriptive methods. Moreover, this study utilized ten samples determined by purposive sampling with consideration the aim of this research is clear, namely to find out the marketing of hydroponics greenhouse products in Greater Malang. In addition, the sample for this study was selected using the snowball sampling method, which sampled the marketing channels of the previous ten samples. The results of this study indicate that the management of hydroponic greenhouse vegetables in Greater Malang begins with the most frequently traded product, in this case, lettuce. Participating marketing institutions included farmers, collecting traders, retailers, restaurant consumers, and end consumers. Level 1 marketing channel is the channel with the most consumers. The marketing functions used are the exchange function, the procurement function, and the facilitating function. Level 0 marketing channels have no marketing margin value because the price farmers receive is identical to that of consumers. Marketing channel level 0 for all commodities and marketing channel level 1 for all commodities are deemed efficient for the farmer's share. The cooperative system among hydroponic greenhouse vegetable sellers in Greater Malang is harmonious, contributing to a healthy market atmosphere.